تقييم نتائج التعلم من خلال مدخل التفسير المتكامل في موضوع المفعول معه للطلبة المشاركين في الندوة الأسبوعية: An Evaluation of Learning Outcomes Using an Integrated Interpretive Approach on the Topic of Al Maful Maahu - Baso, Sitti Ardianti Baso; Mawardi; Rukman AR. Said (Institut Agama Islam Negeri (IAIN) Palopo, 2025)
Evaluation of learning outcomes with intelligence (cognitive) assessment indicators alone is not comprehensive in evaluating participant learning outcomes. This study aims to find out the extent of the influence of the